“It’s always happy to see me”: Exploring LOVOT robots as companions for older adults - Hung, Lillian; Wong, Joey; Wong, Karen Lok Yi; Tan, Kelvin Cheng-Kian; Lou, Vivian Wei-Qun (Journal of rehabilitation and assistive technologies engineering, 2025)
AI-enabled social robots present the potential to resolve the loneliness and social isolation of older adults in long-term care (LTC). There is limited research on how older adults perceive and make sense of these robots and how human-robot companionship is formed. This study investigated older adults' experiences using LOVOT, a social robot. Using an ethnographic study design, we introduced LOVOT robots to a Canadian LTC home for four weekly interaction sessions. Thirty-six residents, seven family members and two healthcare staff participated. Data collection involved observational field notes and conversational interviews. The analysis was guided by ikigai, a Japanese well-being concept. Reflexive thematic analysis identified four key themes. 1) Joy: The robot offers joy and excitement through interactions. 2) Acceptance: For older adults with mobility or cognitive impairments, LOVOT gives consistent positive responses, offering a sense of unconditional acceptance. 3) Creativity: The robot's non-verbal communication allows older adults to grow creative imagination, encouraging personal expression and expanding interaction possibilities. 4) "Not for me": Not all participants like the LOVOT robot. AI-enabled social robots show potential in supporting the psychosocial needs of older adults, which have broader implications for LTC practices and future research directions. Future research should further explore the creative utility of social robots among LTC residents.